Don't swipe me left please! Protocolli e seduzione ai tempi del dating online - Marika Nesi Lammardo (Ocula)
This paper aims to explore the veridictory strategies dating apps employ to enhance user engagement. Central to online dating, the Swipe action - Right Swipe for interest and Left Swipe for disregard - embodies a widely adopted practice. Nevertheless, an increasing number of users express distrust and frustration with these platforms. A field survey in-volving 380 digital interactions allowed to observe the practice in its natural setting, and then to identify their patterns and values. The main findings expose a recursive grammar of seduction (Craving Effect), stemming from a shift in the actantial role of the al-gorithm, which functions as the Addresser. With re-gard to this matter, a sociosemiotics analysis allows for envisioning a schema of the applied strategies: Covalent Discourse, Mimesis, Métis, and Alchemical Discourse.